Effect of Phyllosilicates As Toxin Binder On Productivity, Intestinal Morphology, and Liver Toxicity in Broiler Fed Afb1 Contaminated Feed - Gardika Windar Prahara; Adhe Humaera; Lies Mira Yusiati; Chusnul Hanim; Asih Kurniawati; Ika Sumantri; Ali Agus; Erika Kusumawardani; Muhsin Al Anas (Buletin Peternakan, 2023)
Aflatoxin B1 is a toxin produced by the fungus Aspergillus flavus which reduces the development and function of organs in broilers. The aim of this study was to determine the effect of adding binder toxin from different bentonite to feed contaminated with AFB1 on productivity, intestinal morphology, and liver toxicity in broilers. A total of 60-day old chick male broilers were placed in 12 pens. Each treatment consisted of three replicates, each replicate containing five broilers. Treatment in the study consisted of P0 (control, basal diet, without the addition of AFB1), P1 (P0 + 100 µg/kg AFB1 + 4 g/kg calcium bentonite Type A), P2 (P0 + 100 µg/kg AFB1 + 4 g/kg calcium bentonite Type B), and P3 (P0 + 100 µg/kg AFB1 + 4 g/kg calcium bentonite Type B + kerolite + saponite). Treatment diets were given to broilers from day 22 to 35 (finisher phase). The results showed that the toxin binder on AFB1 contaminated feed had no effect on feed consumption, body weight gain and feed conversion (p>0.05). Addition of toxin binder on AFB1 contaminated feed increased the relative weight of the duodenum (p=0.024), although P3 was not significantly different. Treatments had no effect on villus length, crypt depth, and ratio of villus length to crypt depth (p>0.05), but decreased villus width (p=0.013). The addition of toxin binder tended to decrease the villus area (p=0.055). SGOT and SGPT did not show differences between treatments. AFB1 contamination with the addition of toxin binder showed signs of toxicity on liver histopathological observations. Based on the research, it can be concluded that the addition of binder toxin in feed contaminated with AFB1 can reduce the negative effect on the development of intestinal villus and chemical effect to the liver. Toxin binder Type B has the best efficacy for reduce the negative effect